Effect of synthetic microfiber and viscosity modifier agent on layer deformation, viscosity, and open time of cement mortar for 3D printing application. (14th February 2022) - Sukontasukkul, Piti; Panklum, Kasidet; Maho, Buchit; Banthia, Nemkumar; Jongvivatsakul, Pitcha; Imjai, Thanongsak; Sata, Vanchai; Limkatanyu, Suchart; Chindaprasirt, Prinya
Highlights: Both MF and VMA can effectively prevent initial deformation. MF is more effective than VMA in preventing further deformation after subsequent layers. Both MF and VMA increases the shear stress in viscosity test. Shear stresses allowing mortars to print uniformly were observed around 583 to 608 m.Pa. Abstract: Layer deformation or settlement is one of the important issues for cement printing applications. In this study, synthetic microfibers and viscosity modifier agent were introduced into cement mortar mixture to deal with it. Three types of mortar control or plain mortar, fiber reinforced mortar (FRM), and mortar mixed with viscosity modifier agent (VMA) were tested. For FRM, the fibers were mixed at 4 different proportions (from 0.025 to 0.10% by volume of mortar). For VMA, two mix proportions at 0.1 and 0.5% by weight of binder were used. Series of experiment including flow, mechanical properties, viscosity, printability time, and layer deformation were carried out. Results indicated that both VMA and fiber helped reduce the layer deformation and shorten the open time noticeably. However, while the fiber improved the mechanical properties of mortar, the VMA provided negative effect to the mechanical properties. The shear stress corresponding to the open time of FRM mortars was found.